2004
DOI: 10.1111/j.1600-6143.2004.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Microencapsulated Adult Pig Islets in Mice In Spite of an Antibody Response

Abstract: The aim of this study was to assess the capacity of simple alginate capsules to protect adult pig islets in a model of xenotransplantation. Adult pig islets were microencapsulated in alginate, with either single alginate coats (SAC) or double alginate coats (DAC), and transplanted into the streptozotocininduced diabetic B6AF1 mice. Normalization of glucose levels was associated with an improvement of the glucose clearance during intravenous glucose tolerance tests. After explantation, all mice became hyperglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 44 publications
4
49
1
5
Order By: Relevance
“…Seven days after DNA injection, the mice were anesthetized with pentobarbital sodium (90 mg/kg) and administered a saline or 20% glucose bolus (1.0 g of glucose/kg of body weight) through the retroorbital sinus. This dosage stimulates a physiologic insulin response (from ϳ0.82 to ϳ3.4 ng/ml spike within 5 min, followed by persistent but declining concentrations at 15 min post-injection, see supplementary data obtained from the Diabetes Endocrinology and Research Center Specialized Assay Core Insulin enzyme-linked immunosorbent assay) and does not induce significant hypoglycemia (21,22).…”
Section: Methodsmentioning
confidence: 99%
“…Seven days after DNA injection, the mice were anesthetized with pentobarbital sodium (90 mg/kg) and administered a saline or 20% glucose bolus (1.0 g of glucose/kg of body weight) through the retroorbital sinus. This dosage stimulates a physiologic insulin response (from ϳ0.82 to ϳ3.4 ng/ml spike within 5 min, followed by persistent but declining concentrations at 15 min post-injection, see supplementary data obtained from the Diabetes Endocrinology and Research Center Specialized Assay Core Insulin enzyme-linked immunosorbent assay) and does not induce significant hypoglycemia (21,22).…”
Section: Methodsmentioning
confidence: 99%
“…The spherical configuration of these microcapsules results in a higher surface-tovolume ratio and a higher diffusion rate (4). Furthermore, microcapsules can be injected in large numbers, are durable, and are difficult to disrupt mechanically (5,6). In this area, alginate is and has certainly been the most commonly used polymer to encapsulate islet cells.…”
Section: Microencapsulationmentioning
confidence: 99%
“…In most studies to date, alginate beads were coated with a second layer to reduce the porosity of the capsule membrane (17,28); in some studies, alternating layers of poly-L-lysine and polyornithine were used to surround the alginate core but mechanical instability was described, thereby limiting their application (17,29,30). Several groups have recently reported that encapsulation in simple alginate microbeads can protect pig pancreatic cells against xenorejections in diabetic mice (5,6,31). Although several chemical formulations of alginate (e.g., high-mannuronic/guluronic and high/low viscosity, with or without additional peptide sequences) have been proposed for islet immunoisolation, high-mannuronic alginate was the most suitable to obtain selective impermeability for molecules over 150 kDa and optimal biocompatibility associated with surrounding angiogenesis and sufficient oxygen tension (up to 40 mmHg) (32).…”
Section: Biomaterials For Islet Encapsulation Technologymentioning
confidence: 99%
“…Capsule fibrosis was the most significant problem encountered when utilizing alginate capsules [23,[49][50][51]. Theoretically, immune isolation is achieved by encapsulation of the cells, but some levels of immune rejection and foreign body response still occur.…”
Section: +mentioning
confidence: 99%